Implementation of peatland restoration policies in Jambi Province (case study of the Jambi Provincial Forestry Service) - Cut aziza dewi; Ruslan Abdul Gani; Imam Arifa’illah Syaiful Huda (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
This research is entitled Regional Government Readiness of Jambi Province in Implementing Peatland Restoration Policy. The problem is that Jambi Province is one of the seven provinces that have prioritized peatland restoration since 2016. Therefore, it is necessary to know how prepared they are in implementing the policy. Knowing the efforts made for the implementation of peatland restoration, and knowing the constraints and solutions provided for the implementation of peatland restoration in Jambi Province. This research method uses qualitative research using a case study approach. Data was collected by means of field observations, interviews, and documentation as evidence of the implementation of peatland restoration policies in Jambi Province. The use of data in this study is primary data and secondary data. Based on the research that has been done, it can be concluded that: 1) The readiness for the implementation of peatland restoration policies in Jambi Province is mature and has been running since 2017 by the Regional Peat Restoration Agency under the auspices of the Jambi Provincial Forestry Service. 2) The form of effort from the peatland restoration policy is to carry out three restoration programs, namely rewetting, revegetation, and revitalization which have been implemented by all three. These three programs have also been implemented in several areas such as Tanjung Jabung Timur Regency, Muaro Jambi Regency, and Sarolangun. 3) Obstacles that exist such as pros and cons in the community are trying to be overcome by conducting socialization and explanations about the benefits of peatland restoration that will be carried out.